Pengolahan Kerupuk Cumi Pada Kelompok UMKM DAFALA Di KotaTernate - Abubakar, Yuyun; Serosero, Rugaya H; Abubakar, Salim; Subur, Riyadi; Rina; Sunarti; Fadel, Ariyati H. (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Squid (Loligo sp) is one of the fishery resources from the cephalopod class which has important economic value. The cephalopod class consists f several groups tht are widely consumed, namely squid, cuttlefish and octopus. Squid is an important commercial fishery commodity that is often found in coastal areas of Asia (Sin et al.,2009). Partners are a group of women who often process fish products but are not yet productive in carrying out processing innovations. With conseling methods and training on squid cracker processing. PKM results training un making squid crackers by exploiting the potential of squid resources in the Togafo sub distric,west Ternate sub district went smoothly and the enthusiasm of the participants was high. Enthusiasm for squid crackers products in two color, namely white (without ink) and black (wth ink). PKM activities Increase knowledge and improve community skills and build comunity enthusiasm for entrepreneurship.